(untitled) (Advancements in Homeopathic Research, 2024)
Introduction: Chronic suppurative otitis media (CSOM) is a long-standing infection of a part or whole of the middle ear cleft characterized by ear discharge and a permanent perforation. In homoeopathy, there are various medicines having a sphere of action on suppurative diseases. This is a show case of Mercurius solubilise Homoeopathic remedy for the case of CSOM: Mercurius solubilise is a black oxide of mercury. It affects the whole system, penetrating every organ and tissue and also has a wonderful effect on suppuration. Mercury, in both acute and subacute forms, is the only drug that effectively prevents suppuration. Case summary: This is the case of 24 yr old man who presented with CSOM and was successfully managed with individualized Homoeopathic medicine, Mercurius Solubilis 200c. The case was followed up with documentation of clinical symptoms and investigation findings. In this article, the ultimate aim is to provide the clinician with a homoeopathic tool in the management of CSOM after having satisfactory results in the case.